If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + -3) = 12(x + -5) Reorder the terms: 4(-3 + x) = 12(x + -5) (-3 * 4 + x * 4) = 12(x + -5) (-12 + 4x) = 12(x + -5) Reorder the terms: -12 + 4x = 12(-5 + x) -12 + 4x = (-5 * 12 + x * 12) -12 + 4x = (-60 + 12x) Solving -12 + 4x = -60 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. -12 + 4x + -12x = -60 + 12x + -12x Combine like terms: 4x + -12x = -8x -12 + -8x = -60 + 12x + -12x Combine like terms: 12x + -12x = 0 -12 + -8x = -60 + 0 -12 + -8x = -60 Add '12' to each side of the equation. -12 + 12 + -8x = -60 + 12 Combine like terms: -12 + 12 = 0 0 + -8x = -60 + 12 -8x = -60 + 12 Combine like terms: -60 + 12 = -48 -8x = -48 Divide each side by '-8'. x = 6 Simplifying x = 6
| p-9=-6p-3 | | 2x+20+4x-10=180 | | 3(x+4)-4=3(x-4) | | 0.25y=12 | | 3(x-4)-4=3(x-4) | | lnx=22.87 | | 2.5(fk+2)=12k | | 4x+3x=182 | | y^6-3y^4-y^3+3y^2-1=0 | | -6(6x-1)=-36x-6 | | 144x^2-1/4=0 | | y-9=-1(x-16) | | 50-2x=15+3x | | 14(v+4)-2v=3(4v+4)-18 | | y-9=-0.66(x-16) | | y-9=-(2)/(3)(x-16) | | y-9=-2/3(x-16) | | 3x-208=x/9 | | 5(x+7)=-30(x+2) | | -5(x+4)+3x+5=5x+12 | | -7(x+3)+3x+7=5x+11 | | ((d-4)/(4))^(2)=64 | | 1/3*6h=20 | | -3(2x+5)=7x+1 | | 7(x-7)+2=9-(x+6) | | 3(x-3)=2-8x | | x-3=.75(2-x)+6 | | 2h-3h=15 | | X/0.4=11.25 | | 11x^2=44x | | 5x/x=(8x^3)/x^2 | | Y-4=-8.4 |